Manifestasi Tuhan Dalam Tiga Agama: Islam, Hindu Dan Kristen - Fatkhurrohman, Abdul Azis (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article is intended to explore the concept of God's manifestation in three different religions. The agreement of each religion/belief on the Godhead, has become a guide for each of its adherents. On the other hand, the differences of other derivative concepts become very open to be studied in the comparative area. The Oneness of God, which is explained and agreed upon by all religions, lowers the conception and assertiveness shown by His own Essence to be understood upon His existence through His manifestation. It is in this area of manifestation that there is a distinction from each belief to